Pemberian Kombinasi Vitamin C dan E Peroral Memperbaiki Kerusakan Hepar Akibat Paparan Rokok Kretek Sub Kronik - Muliartha, I Ketut Gede; Sriwahyuni, Endang; Yuliawati, Yuliawati (Fakultas Kedokteran Universitas Brawijaya, 2009)
ABSTRACTFree radicals in cigarette smoke can destroy tissue and cells of the body. The activity of free radicals can bereduced by antioxidants from external and internal. The objective of this research is to investigate the effectsof vitamin C and vitamin E combination on the histopathology of rat liver exposed by subcronic cigarettesmoke. This research using true experimental study with post test only control group design. The sample othis research we used 32 Wistar rat, ages between 2-3 months, weight 150-200 grams divided 8 groupedCigarette smoke exposed for 10 weeks. Parameter will be measured is the number of liver cells damage(necrosis). Data analysis uses the One-Way ANOVA method followed by Turkey test. The result show thenumber of liver cells damage are significantly decrease. The conclution vitamin C and vitamin E combinationdecrease the number of the liver cells damage of the rat liver, that has been exposed to subcronic cigarettesmoke at optimal doze 0,20 mglg bw vitamin C and 0,04 lUlg bw vitamin E.Keywords: vitamin C, vitamin E, cigarette smoke, liver cells damage.